2002
DOI: 10.3354/meps230225
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of Calanus chilensis off Mejillones Peninsula (northern Chile): ecological consequences upon coastal upwelling

Abstract: The Mejillones Peninsula upwelling system (northern Chile) appears to be a natural laboratory, suitable to test hypotheses concerning variability of copepod growth in nature. In this zone, in January 2000, we collected zooplankton samples inside and outside of an upwelling plume to assess differential responses of copepodid Calanus chilensis to spatial distribution of temperature, chlorophyll a (chl a), current field and dissolved oxygen (DO). We studied variability of prosome length (PL), dry weight (DW), oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 27 publications
1
18
2
Order By: Relevance
“…This pattern may reXect the availability of food since primary production is at maximum in a depth of 15 m (Giraldo et al 2002). Furthermore, the oxygen concentration measured during the present 7-year study always exceeded 1 ml l ¡1 at the 10 m stations, whereas lower oxygen concentrations at 20 m depth might have reduced abundances and limited the distribution of some species (FAO 1975), leading to a virtual absence of macrobenthos at deeper bottoms forming part of the OMZ.…”
Section: Abundancementioning
confidence: 62%
See 3 more Smart Citations
“…This pattern may reXect the availability of food since primary production is at maximum in a depth of 15 m (Giraldo et al 2002). Furthermore, the oxygen concentration measured during the present 7-year study always exceeded 1 ml l ¡1 at the 10 m stations, whereas lower oxygen concentrations at 20 m depth might have reduced abundances and limited the distribution of some species (FAO 1975), leading to a virtual absence of macrobenthos at deeper bottoms forming part of the OMZ.…”
Section: Abundancementioning
confidence: 62%
“…Several studies have shown the existence of cold upwelled water in nearshore zones (e.g. Fonseca 1989;Escribano 1998;Marín et al 2001;Giraldo et al 2002), sustaining large biomasses of small pelagic Wsh (Alheit and Bernal 1993).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species occupied the largest part of this area and was highly influenced by subtropical waters with low temperatures and salinity. This species is typical of the Humboldt Current System (Giraldo et al, 2002;Escribano et al, 2004;Hidalgo and Escribano, 2007;Ayón et al, 2008) and location of catches in this area indicates a displacement from the coast of Chile-Peru to Ecuador, coinciding with the proposal of Arcos and Fleminger (1986). However, in this study, C. chilensis distribution extended farther northward than in normal years (Arcos and Fleminger, 1986), offering evidence that the influence of the Humboldt Current reached farther north in the equatorial Pacific during the cold event of 2001.…”
Section: Discussionmentioning
confidence: 67%